RESEPSI HADIS DALAM FILM PENDEK “KAYA TAPI MISSQUEEN” CHANNEL YOUTUBE ISLAMIDOTCO - Muhammad Ragil Hasan (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2022)
This article discusses the reception of living hadith studies in the film